A Gordian knot: Nomenclature and taxonomy of Heterocapsatriquetra (Peridiniales: Heterocapsaceae). Issue 1 (17th February 2018) - Prado, Jefferson; Lendemer, James; Tripp, Erin; Gottschling, Marc; Tillmann, Urban; Kusber, Wolf-Henning; Hoppenrath, Mona; Elbrächter, Malte
Abstract: In the course of polyphasic taxonomic work in the dinophytes, we became aware of a fundamental misapplication of the name Glenodinium triquetrum (now represented conceptually by a species of Kryptoperidinium), when Stein assigned it to Heterocapsa. Possible solutions involve a conflict between retaining Ehrenberg's epithet in its correct application in the interest of priority and preserving current usage of Heterocapsa. However, we do not achieve a consensus on how to disentangle this Gordian knot, underlining that this is not a regular case of taxonomic confusion. We intend to stimulate a more general discussion about best practices in such cases, balancing between the interest of nomenclatural practicability and the respectful acknowledgement of scientific work, even if it was conducted many years ago.